2020
DOI: 10.1136/bmjdrc-2020-001190
|View full text |Cite
|
Sign up to set email alerts
|

Insulin pricing and other major diabetes-related concerns in the USA: a study of 46 407 tweets between 2017 and 2019

Abstract: IntroductionLittle research has been done to systematically evaluate concerns of people living with diabetes through social media, which has been a powerful tool for social change and to better understand perceptions around health-related issues. This study aims to identify key diabetes-related concerns in the USA and primary emotions associated with those concerns using information shared on Twitter.Research design and methodsA total of 11.7 million diabetes-related tweets in English were collected between Ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…Along with big data growth, machine learning and data mining techniques such as text mining and natural language processing are constantly evolving and are thus increasingly used in the field of public health research based on SM [71][72][73]. These techniques can be particularly interesting to analyze social media data and, for instance, to develop sentiment or topic analysis among a specific population [19,74] or to predict epidemics [75]. Twitter is mainly used for such work because Twitter developed a streaming application programming interface.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Along with big data growth, machine learning and data mining techniques such as text mining and natural language processing are constantly evolving and are thus increasingly used in the field of public health research based on SM [71][72][73]. These techniques can be particularly interesting to analyze social media data and, for instance, to develop sentiment or topic analysis among a specific population [19,74] or to predict epidemics [75]. Twitter is mainly used for such work because Twitter developed a streaming application programming interface.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Of note, similar analyses of Twitter use by people with (all types of) diabetes were conducted recently by Ahne et al [ 22 ]. While our study is both conceptually and analytically similar to that of Ahne et al [ 22 ], we expand on the methodology and research questions in two ways: first, data collection was driven by the goal of including members of the type 1 DOC, rather than tweets covering a specific topic. This allows us to generate a more holistic view of these users’ lives and concerns.…”
Section: Introductionmentioning
confidence: 74%
“…Other machine learning–type methods have also been used to analyze web-based behavior. Relevant to this study, Ahne et al [ 22 ] identified tweets related to diabetes through the use of keywords and hashtags and summarized the topics therein using k -means clustering. They identified a set of 30 topics, several of which were variations on concerns regarding insulin pricing and availability.…”
Section: Introductionmentioning
confidence: 99%
“…People with DM2 express concern due to insulin prices, therefore, it generates a negative impact on their state of mind [11], since personal care and living with complications related to DM2, causes negativity at a psychosocial level affecting health in it.…”
Section: Discussionmentioning
confidence: 99%
“…Although, when you have DM2 and other cardiovascular diseases that occur at a younger age, they tend to develop ASTESJ ISSN: 2415-6698 aggressively, compromising the health of the diabetic person [11]. It can also lead to low life expectancy and this as a consequence causes a decline in quality of life [12].…”
Section: Introductionmentioning
confidence: 99%